THE BENEFITS OF STRENGTH TRAINING ON CHANGES OF PHYSIOLOGICAL SYSTEMS ASSOCIATED HEALTH IN THE THIRD AGE (Fiep Bulletin - online, 2013)
Statistical data show that the population of aged Brazilians is growing each year and that several factors in these people's daily lives contribute to the loss of muscular strength with age. The aim of this paper is investigate and analyze through bibliographical references, the benefits and limitations of Strength Training for individuals in more advanced age groups and the importance of physical activity for such age groups to help ease symptoms of osteoporosis, Diabetes Mellitus and obesity. During recent years the benefits of such Strength Training during the ageing process has been proven. In fact, some investigators have shown that some individuals of over 90 (ninety) years of age can still obtain an increase in strength capacity during a training period of just eight weeks, which results in better functional capacity and thus also an improvement in quality of life. The first research based on training for older people was focused largely on the concept of preventing the wasting of muscle mass and age-related loss of strength. As a result and by default, low-intensity training was a favorite option, thus ruling out a priori any possibility that an older person could withstand, or even benefit from, higher-intensity sessions of Strength Training. Many reasons were brought forward to support this stance, but very little research was actually carried out, and virtually nothing was known about how the organisms of older people react when subjected to a program of Strength Training of whatever intensity. Underscoring the importance of older people's adaptability to physical exercise, we find the resulting metabolic reactions and structural and functional changes lead to a better performance of day-to-day activities, and so Strength Training serves as a powerful instrument for the promotion of better health of older people a basic strategy to be considered in a process of healthy ageing.